Analisis Implementasi Akad Murabahah Terhadap Pembiayaan Barang Dan Jasa Pada Usaha Pembiayaan Sumber Jaya Di Desa Pasir Ringgit Kecamatan Lirik Kabupaten Indragiri Hulu - Arif Firdaus Siahaan; Muhammad Apis Daulay; Desmi Satriana (CV. ITTC INDONESIA, 2025)
This study aims to analyze the implementation of the Murabahah contract in the financing of goods and services at Usaha Pembiayaan Sumber Jaya, located in Desa Pasir Ringgit, Kecamatan Lirik, Kabupaten Indragiri Hulu. Murabahah is one of the contracts in Sharia financing that emphasizes price transparency and the seller’s ownership of goods before they are sold to the buyer. This research is driven by the need to ensure that the application of Murabahah truly adheres to Sharia principles, particularly in terms of ownership, the contract process, and transparency between the financier and the customer. This study employs a descriptive qualitative approach with data collected through observation, interviews, questionnaires, and documentation. The respondents include management and customers of Usaha Pembiayaan Sumber Jaya, selected through purposive sampling. The data were analyzed by comparing the practices in the field with the theoretical and fundamental principles of the Murabahah contract. The results indicate that the implementation of the Murabahah contract at Usaha Pembiayaan Sumber Jaya generally aligns with Sharia principles, such as the financier’s prior ownership of goods and price transparency. However, some challenges remain, including a lack of understanding among some customers regarding the details of the contract. The financier also faces issues such as late payments. Moreover, the study found that Murabahah was also used for service financing, which is not in accordance with Fiqh principles, as Murabahah should only be used for transactions involving tangible goods. In addition, the financing institution under study has not yet obtained formal legal status from financial authorities or a Sharia supervisory body.